Analisis Pengendalian Kualitas dengan Menggunakan Metode Basic Seven Tools pada Produksi Telur Puyuh di UMKM Bani Marfu Farm - Irawan, Ikhsan Dony; Wahyudin, Wahyudin; Kusnadi, Kusnadi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study was conducted to address the issue of product defects at UMKM Bani Marfu Farm, which negatively impacts the company’s revenue and market competitiveness. The background of the study highlights that product quality is a crucial factor in business success, with higher quality increasing consumer demand. This research employs the Basic Seven Tools approach in quality control to reduce defect rates in quail egg production. The method is applied through production data analysis and identification of the root causes of defects. The results show that implementing the Basic Seven Tools effectively reduces product variability, improves the quality of the quail eggs produced, and significantly strengthens UMKM Bani Marfu Farm’s market competitiveness.